Intimate relationships and social change : the dynamic nature of dating, mating, and coupling - Scott, Christina L.; Blair, Sampson Lee (Contemporary perspectives on family research ;, 2017)
Over the past few decades, there has been a dynamic world-wide societal shift away from traditional routes for finding a partner and establishing intimate relationships. This multidisciplinary volume investigates the impact of online dating and the role of technology in relationship formation; the nature of cohabitation and its relative meaning with marriage; assortative mating patterns; the role of parents and siblings in the selection of a partner; gender and sexuality within dating and mating; evolving forms of non-traditional marriage; the interplay of personality and sociodemographic traits within partner selection; and the role of race, ethnicity, and religion in dating and mating. Together, this collection provides a unique and truly global collection of research on the nature of dating, mating, and coupling, as they occur across a variety of cultures.